Stability and Shelf-Life of Plasma Bubbling Treated Cow Milk: Life Sciences-Food science and Technology - Dash, Samarpita; Jaganmohan, R. (International Journal of Life Science and Pharma Research, 2022)
The demand of consumers for naturality of food with minimal processing was forced to the scientists for the discovery of non-thermal plasma which is a new technology for the preservation and decontamination of food products. The present study was conducted for the scrutinization of microbial and physicochemical characteristics of plasma bubbled raw cow milk and an extensive comparison was observed for boiled raw cow milk, commercially (pasteurised and UHT) milk. Further, storage study (shelf-life) was done for the plasma bubbled raw cow milk and compared with raw cow milk sample (control). The bubbling of plasma was generated at a voltage of 200V, the flow rate of air 10 litres/hour (L/h) and applied to fresh cow milk for 5, 10, and 15 minutes (min) of time with a volume of 100 mL of the sample operated at room temperature. A declined in microbial cell was observed for coliform and yeast at 200V, 10L/h, 15 min time interval. The pH value of 15 min plasma bubble treated sample was increased significantly to 6.85. While, a slight decrease in value was noticed in total soluble solids (TSS) and titratable acid (TA) after exposure to plasma bubbling. Further, a nondetrimental effect was observed for the nutrient content of plasma bubbling of milk. The result indicates that plasma bubbling at generated at 200V, 10L/h,100mL,15 min treatment enhances the milk quality. However, plasma bubbling: based on indirect dielectric barrier discharge (DBD) may use as a successful decontamination technology without affecting the physicochemical properties which could have a future perspective on industrial food applications.